Amino‐Functionalized Graphene Quantum Dots as Cathode Interlayer for Efficient Organic Solar Cells: Quantum Dot Size on Interfacial Modification Ability and Photovoltaic Performance. Issue 3 (29th November 2018) - Wang, Shichao; Li, Zuojia; Xu, Xiaopeng; Zhang, Guangjun; Li, Ying; Peng, Qiang
Abstract: In this work, a series of amino‐functionalized graphene quantum dots (AF‐GQDs) with different quantum dot sizes are prepared successfully and employed as the cathode interfacial layers (CILs) for fabrication of efficient organic solar cells (OSCs). The effect of quantum dot size on the interfacial modification ability and photovoltaic performance is investigated in detail. By varying the particle size of AF‐GQDs, the work function of the cathode and the conductivity of CIL can be finely tuned. M‐GQD with the medium size achieves the best balance of interfacial modification and conductivity, giving rise to the best power conversion efficiencies both in fullerene and nonfullerene OSCs (poly[[4, 8‐bis[(2‐ethylhexyl)oxy]benzo[1, 2‐b:4, 5‐b′]dithiophene‐2, 6‐diyl][3‐fluoro‐2‐[(2‐ethylhexyl)carbonyl]thieno[3, 4‐b]thiophenediyl]] (PTB7):[6, 6]‐phenyl‐C71 ‐butylic acid methyl ester (PC71 BM) blend: 10.14%; poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b′]dithiophene)‐co‐(1, 3‐di(5‐thiophene‐2‐yl)‐5, 7‐bis(2‐ethylhexyl)benzo[1, 2‐c:4, 5‐c′]dithiophene‐4, 8‐dione)] (PBDB‐T):3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐d:2′, 3′‐d′]‐s‐indaceno[1, 2‐b:5, 6‐b′]dithiophene) (ITIC) blend: 11.87%; and poly[(4, 8‐bis(5‐(tripropylsilyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b′]dithiophene)‐co‐(5, 6‐difluoro‐2‐(2‐hexyldecyl)‐4, 7‐di(thiophen‐2‐yl)‐2H‐benzo[d][1, 2, 3]triazole)] (J71):ITIC blend: 12.81%). This work not only provides a new type of high‐performance CIL materials but also demonstrates a simple way for fine‐tuning the interfacial modification ability and the conductivity via just controlling the quantum dot size of AF‐GQDs. Abstract : A series of amino‐functionalized graphene quantum dots (GQDs) with different particle size, small‐GQD, medium‐GQD, and large‐GQD, are prepared for efficient fullerene and nonfullerene organic solar cells. medium‐GQD with medium quantum dot size achieves the balance of interfacial modification ability and conductivity, giving rise to the best device efficiencies both in fullerene and nonfullerene organic solar cells.